Penerapan Aplikasi Simulasi Ujian Akhir Semester Pada SMU Negeri I Tanjung Raja Berbasis Online - dwi yunita, hilda; Tarnando, Kiki; Winarko, Triyugo (Journal Software, Hardware and Information Technology, 2023)
The exam is a form of evaluation that is used to assess the achievement of the lessons taught by the teacher to students. In addition to the national exam, there is an end-of-semester exam at the school. Where the end of semester exams are still carried out conventionally or in writing such as at Tanjung Raja 1 Public High School. This resulted in a slow assessment process carried out by the teacher and a waste of paper and ink in doubling questions. Therefore, an application was created that can be used to carry out online final semester exam simulations. So that it can overcome all the problems that exist in the final semester exams at SMA Negeri 1 Tanjung Raja, North Lampung.